PENERAPAN UNDANG-UNDANGAN NOMOR 23 TAHUN 2004 TERHADAP KORBAN KDRT (Studi Kasus Putusan Nomor XXX/Pid.Sus/2020/PN.Mrn) - Kansil, Christabel Flora Kansil; Hendri Jayadi; Mery. R. L. Sibarani (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
Violence occurs not only in public areas but also in domestic areas that lead to domestic violence. Ironically, women—especially wives—are the most often victims of domestic violence. This study conducted to comprehend the implementation of Law Number 23 of 2004 on the Elimination of Domestic Violence in the case of the Corruption Eradication Commission, as well as to investigate the legal ramifications of the Corruption Eradication Commission’s criminal law. The Civil Law Law, Law Number 23 of 2004 on the Elimination of Domestic Violence, and Meureudu District Court Decision Number XXX/Pid. Sus/2020/PN were the key legal sources used in this study. The KDR Indonesian language dictionary contains information relating to the implementation of the law, including Mr. and secondary legal documents. This research is a normative legal study employing library techniques using the mentioned resources. The results of this study suggest that Law Number 23 of 2004 on the Elimination of Domestic Violence has regulated what is included in domestic violence (KDRT). This includes physical, psychic, and sexual violence. Then, the next finding is based on the District Court Decision Number: XXX/Pid. Sus/2020/PN.mr that KDRT occurred.